Efecto de los tratamientos térmicos de recocido, temple, revenido y austempering sobre la dureza y microestructura de una fundición blanca hipoeutéctica - Rodríguez Saavedra, Elizabeth. (2016)
The effects of heat treatments on the hardness and microstructure of a hypoeutectic white iron, which is compost by 2.52% C, 1.51% Si, 0.20% Mn, 0.01% S y 0.02% P, was studied in the physical metallurgy laboratory. White iron square bars 12 mm x 12 mm x 200 mm long was used, supplied by nodular iron SA (FUMASA), which were heated to austenitizing temperature of 950 ° C for 2 hours under these conditions and heat treatment of annealing, quenching, tempering and Austempering were performed. The experimental results showed that with the annealing heat treatment was get it a malleable cast iron ferritic structure which consists of irregular nodules of graphite and ferrite (matrix). With the heat treatment of quenching, a high level of hardness is obtained (605.30 HB), due to because the microstructure is formed by plates acicular cementite and martensite. With decreases tempering hardness (Hardness) as the temperature increases, due to the martensite is transformed into tempered martensite. Finally the hardness decreases austempering (Hardness) as the process temperature increases due to lower bainite transformation (Bi) to upper bainite (Bs). We concluded that the heat treatments applied to the hypoeutectic white cast, significantly affect the hardness and microstructure of the casting.